2021
DOI: 10.1101/2021.07.19.21260767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children with SARS-CoV-2 in the National COVID Cohort Collaborative (N3C)

Abstract: Importance: SARS-CoV-2 Objective: To determine the characteristics, changes over time, outcomes, and severity risk factors of SARS-CoV-2 affected children within the National COVID Cohort Collaborative (N3C) Design: Prospective cohort study of encounters with end dates before May 27th, 2021. Setting: 45 N3C institutions Participants: Children < 19-years-old at initial SARS-CoV-2 testing Main Outcomes and Measures: Case incidence and severity over time, demographic and comorbidity severity risk fac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…With the increase in the number of cases of COVID-19, the need to better understand this pathology appears increasingly urgent; in this sense, identifying risk factors of severity certainly represents one of the most important objectives. As for the general characteristics, our data confirm what has already been reported in the literature, highlighting how older age and the diagnosis of MIS-C are more frequently present in patients admitted to the PICU [ 21 ]. On the other hand, there were no statistically significant differences according to gender and the presence or absence of comorbidities, differently from what was reported in other studies [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…With the increase in the number of cases of COVID-19, the need to better understand this pathology appears increasingly urgent; in this sense, identifying risk factors of severity certainly represents one of the most important objectives. As for the general characteristics, our data confirm what has already been reported in the literature, highlighting how older age and the diagnosis of MIS-C are more frequently present in patients admitted to the PICU [ 21 ]. On the other hand, there were no statistically significant differences according to gender and the presence or absence of comorbidities, differently from what was reported in other studies [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…We found that neuroimmune complications were exceedingly rare, whereas MIS-C occurred in 0.05% of confirmed SARS-CoV-2 infections, which is similar to other population based estimates. 28 29 30 Previous studies have identified obesity and black and Hispanic race as important risk factors for severe covid-19 and MIS-C. 24 25 30 This needs to be considered when generalising our results, as Denmark is predominantly a society of white ethnicity with a low prevalence of childhood obesity. 31 …”
Section: Discussionmentioning
confidence: 85%
“…22 Compared with the few previous studies providing population based data on the risk of hospital admission after SARS-CoV-2 infection, the reported risks were similar to those of Israel and Spain (0.2% to 0.5%), but lower than those reported from the UK (1.3%) and US (5.7%). 7 23 24 25 Both the case fatality rate and the risk of hospital admissions are, however, influenced by access to testing for SARS-CoV-2 and are likely to be overestimates of the true risk. Recent Danish SARS-CoV-2 seroprevalence studies have estimated that the true prevalence of SARS-CoV-2 infection among adolescents is up to threefold higher than that detected by national RT-PCR tests.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the UK recently decided to restrict vaccination to adolescents who are at risk of severe COVID-19 and to those who are household contacts of immunosuppressed patients (https://www.gov.uk/government/news/ jcvi-issues-advice-on-COVID-19-vaccination-of-children-and-young-people, accessed on 31 July 2021) As for any vaccine in any target population, the decision to recommend and implement COVID-19 vaccination of adolescents and younger children is based on benefit-risk analyses [120][121][122][123]. Although most children remain asymptomatic, 6% of children are hospitalized; 13% of those hospitalized meet the criteria for severe disease with a fatality rate of 1%, while others suffer from prolonged symptoms (long COVID) and could, therefore, benefit from vaccination [124]. This benefit is stronger for vulnerable children who are at risk of severe COVID-19.…”
Section: Vaccination Of Childrenmentioning
confidence: 99%